Constitutionality of the Right to Information: Proportionality Test of Aircraft Accident Investigation - Ilyas, Anshori; Yunus, Ahsan; Fitriyani, Desi; Taufiq, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Right to information is one of the constitutional rights guaranteed by the constitution. The compliance of a right to information for citizens is done by considering the established limitations. A problem arises when the public considers the disproportionate limitations that seem unilateral. This is related to confidential information on the aircraft accident investigation result. This research was aimed to analyze the proportionality test of confidential information from the aircraft accident investigation result Lion Air JT-610. The method uses a normative method with statute, case, conceptual and comparative approaches. The result of research indicated that confidential information from aircraft accident investigations was not applied proportionally and derogated citizen’s constitutional rights. Confidential information from the aircraft accident investigation result Lion Air JT610 (Boeing MAX-8) is not based on the principle of proportionality test.